Civil Apparatus Formation Management Strategy to Improve Public Service Effectiveness at the Pasuruan City Regional Personnel Agency - Braja Manastha Winduaji; Fedianty Augustinah; Eny Haryati (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
This research seeks to examine the approach to managing civil servant training to enhance public service efficiency at the Regional Civil Service Agency (BKD) of Pasuruan City. This research is rooted in the bureaucratic difficulties encountered by local governments, especially the disparity between organizational demands and the presence of qualified staff. This situation results in delays in service, reduced productivity, and ineffective management of human resources. The study utilizes a qualitative descriptive method, gathering data via comprehensive interviews, firsthand observations, and analysis of policy documents. The results indicate that the state civil servants formation management approach at BKD Pasuruan emphasizes three main elements: workforce planning based on competencies, employee redistribution according to performance, and strengthening evaluation systems oriented towards results. These tactics have enhanced bureaucratic effectiveness and expedited public service operations. The research additionally reveals that effective execution relies on adaptive leadership, a cooperative work environment, and a dedication to service innovation. In summary, an effectively designed, flexible, and results-oriented state civil servants formation management approach can act as a template for enhancing local administrative capabilities to deliver efficient, professional, and enduring public services.